2019
DOI: 10.1109/tdei.2018.007752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal ageing on space charge in ethylene propylene rubber at DC voltage

Abstract: To understand the space charge characteristics of ethylene propylene rubber (EPR) used in MV/HV power cables under thermal stress, the space charge profile is measured by the pulsed electro-acoustic method under 20 kV/mm at 120 and 160 °C. The complex permittivity and physicochemical properties at the different ageing stages are measured and analyzed for an understanding of the effects of thermal ageing on space charge characteristics. The trap properties of EPR during thermal ageing is calculated and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…where, J e (t) and J h (t) stand for the current density of electrons and holes on the boundary. A refers to the Richardson constant that approximates to 1.2 � 10 6 A/m 2 •K 2 . ω e and ω h refer to injection barriers (effective work function) of the two carriers.…”
Section: Charge Injection Theory Of Bct Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where, J e (t) and J h (t) stand for the current density of electrons and holes on the boundary. A refers to the Richardson constant that approximates to 1.2 � 10 6 A/m 2 •K 2 . ω e and ω h refer to injection barriers (effective work function) of the two carriers.…”
Section: Charge Injection Theory Of Bct Modelmentioning
confidence: 99%
“…The accumulation and transport of space charges can cause the degradation or even breakdown of the oil-paper insulation. Many of methods for measuring space charge in dielectric materials have been proposed so far, such as the pulsed electroacoustic (PEA), pressure wave propagation (PWP) [1,2], etc. Meanwhile, the numeric calculation technique, as an important auxiliary technique of the experiment method, has been used for improving the optimal design of electrical insulation in computational high-voltage engineering.…”
Section: Introductionmentioning
confidence: 99%
“…During polarization phase, the impurity ions move along the direction of the electric field and cause the increase of polarization current. In addition, the previous studies have shown that small physical defects will gradually form in EPR such as the air gap in the order of micrometer [19]. Moreover, the thermal aging accelerates the fracture of EPR molecular chain, resulting in the increase of defects, as well as the trap energy level and trap density.…”
Section: A Polarization and Depolarization Currentmentioning
confidence: 99%
“…Men et al aged EPR material at a temperature of 120 • C for 120 days and measured the space charge profile. This indicated that negative charge accumulated near both electrodes and that the amount first rose and then fell over time [9]. Yin et al found that when LDPE and EPR were in close contact, their interface could easily accumulate space charge.…”
Section: Introductionmentioning
confidence: 99%